PREFERENSI FAKTOR – FAKTOR KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN DEMAK - Saraswati, Yosiana Desi; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2014)
This study used four performance factors, namely motivation, ability and skills of employees, compensation, and leadership. The samples in this study were employees of the Perusahaan Daerah Air Minum (PDAM) Kabupaten Demak totaling 60 employees. The analysis used in this study is the Spearman Rank Correlation Test, Test of Non - Parametik Mann Whitney and Kruskall Wallis test and Duncan test.The results showed that there is a correlation factor of four fairly strong performance between male employees and female employees. Of the four performance factors, male and female employees have different preferences as a performance factor of the first order. Employees working men choose a motivating factor as the main factors that can affect their performance, while female employees choose leadership factors as the main factors that can affect performance. In general, employees are men and women have the same preferences for factors abilities and skills of third place, and the compensation factor ranks last ( fourth ). Based on the level of education, reflects differences in appearance of individual preferences and abilities. While the preference of motivation, compensation and leadership is no different. School employees have a preference ranking of job motivation factor higher than the D3 and S1.